Power of the fire dragon - West, Tracey, 1965-; Howells, Graham (2015)
When the king decides to take the dragons to Arkwood to visit Queen Rose, Rori, Drake, and their dragons are left behind--so when the evil wizard Maldred attacks the castle riding a giant four-headed dragon that spits poison, the two young dragon masters and their dragons are forced to defend the castle by themselves.
Appeals to 1st-3rd graders.
Reading level 2
Keywords: Dragons -- Juvenile fiction; Wizards -- Juvenile fiction; Magic -- Juvenile fiction; Adventure stories; Dragons -- Fiction; Wizards -- Fiction; Magic -- Fiction; Adventure and adventurers -- Fiction